Greek myths, part II myth as science, religion and drama - Highet, Gilbert 1906-1978; Barnes, John (The humanities classical civilization, 1971)
Uses dramatizations and animation to present Greek myths as primitive fiction, primitive history, primitive science, primitive psychology, early attempts to understand the origins of the universe, and as a basis for drama and religious inquiry.